Investigation Into Effect Of Crude Mixture Of Abrus Precatorius Seed On Hypothalamopituitary Gonadal Axis And Development Of Antifertility In Male Rats - Talukder, S; Hossain, MA; Sarker, S; Khan, MAH (Bangladesh Journal of Agricultural Research, 2011)
To evaluate the antifertility effect of crude mixture of A. precatorius seeds at the dose level of 50 mg/kg body weight in adult male rats, after oral administration to male rats for 40 days, the rats were sacrificed and hormonal profiles, serum biochemistry, sperm count and histological changes were recorded. A sharp decrease in the serum levels of testosterone (0.70 ± 0.17 ng/ml), FSH (0.70 ± 0.22 lU/L), and LH (0.87 ± 0.35 IU/L) was detected compared to control (FSH, LH and testosterone levels 0.93 ± 0.15 ng/ml, 0.76 ± 0.28 IU/L, 1.44 ± .011 IU/L, respectively). A significant reduction of epididymal sperm count (2.34 million/mL) was noted in treated rats as compared to control group (7.87 million/mL). Histology of testes showed marked atrophy of the testes, which was characterized by disruption of the seminiferous epithelium and atrophy of the Leydig cells. Crude mixture of A. precatorius seed has a negative impact on male reproductive functions. It might be suggested that crude mixture of A. precatorius seeds might have antifertility property for male rats. Keywords: Abrus precatorius; antifertility; male rat; testosterone. DOI: http://dx.doi.org/10.3329/bjar.v36i1.9234 BJAR 2011; 36(1): 103-109